2020
DOI: 10.1111/jfb.14257
|View full text |Cite
|
Sign up to set email alerts
|

Male mate choice for a female ornament in a monogamous cichlid fish, Mikrogeophagus ramirezi

Abstract: Male ram cichlid, Mikrogeophagus ramirezi, spent significantly more time associating with animated female images compared to static images of the same female, indicating that males of the species reliably respond to computer‐animated images of conspecific females. Female M. ramirezi temporarily display a pink‐coloured belly, and this study showed that males spent significantly more time associating with animated female images displaying a pink‐coloured belly compared to animated female images with pink belly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although we could only measure some components of the courtship behavior and not the actual preference, the ability of adjusting song to the potential mate would fit with theories on male mate choice suggesting that males would benefit from displaying more elaborately toward females with higher fecundity. Male mate choice has been demonstrated in various taxa like in fishes and arthropods ( Pollo et al 2019 ; LaPlante and Delaney 2020 ), but was scarcely investigated and proved in birds ( Hill 1993 ; Wolf et al 2004 ; Pryke and Griffith 2007 ; Holveck et al 2011 ). Only a single study focused on song and found that captive Bengalese finch ( Lonchura striata domestica ) males sang with systematically different quantity and quality for different unmated females ( Heinig et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could only measure some components of the courtship behavior and not the actual preference, the ability of adjusting song to the potential mate would fit with theories on male mate choice suggesting that males would benefit from displaying more elaborately toward females with higher fecundity. Male mate choice has been demonstrated in various taxa like in fishes and arthropods ( Pollo et al 2019 ; LaPlante and Delaney 2020 ), but was scarcely investigated and proved in birds ( Hill 1993 ; Wolf et al 2004 ; Pryke and Griffith 2007 ; Holveck et al 2011 ). Only a single study focused on song and found that captive Bengalese finch ( Lonchura striata domestica ) males sang with systematically different quantity and quality for different unmated females ( Heinig et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ram cichlid is a small (4–5 cm long) freshwater fish from the tropical regions of South America (Venezuela and Colombia) 34 . From the aquarium hobby literature and from what we know about its natural habitat 35 , it appears to require similar water conditions (water chemistry and temperature) as the zebrafish 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unlike zebrafish, the ram cichlid moves slowly and thus its behavioural responses can be more easily tracked using commercial video-tracking systems as well as event recording-based methods 37 . Also notably, in nature and in the laboratory, the ram cichlid has been observed staying close to objects, moving into crevices or in between rocks 34 . Thus, unlike the zebrafish, it does not prefer open water and, we speculate, should be more comfortable in the confinement of mazes and other small tanks employed for learning and memory studies with fish.…”
Section: Introductionmentioning
confidence: 99%